Revisiting the home bias puzzle: Downside equity risk - Rachel A. Campbell; Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
Deviations from normality in financial return series have led to the development of alternative portfolio selection models. One such model is the downside risk model, whereby the investor maximizes his return given a downside risk constraint. In this paper we empirically observe the international equity allocation for the downside risk investor using 9 international markets' returns over the last 34 years. The results are stable for various robustness checks. Investors may think globally, but instead act locally, due to greater downside risk. The results provide an alternative view of the home bias phenomenon, documented in international financial markets.
urn:nbn:de:hebis:30-38057
Keywords: G11; G12; G15; 330; Asset Pricing; Home Bias; Downside Risk; Prospect Theory; Capital Asset Pricing Model; Home Bias Puzzle; Prospect Theory